Diseases Caused by Xylella fastidiosa in Prunus Genus: An Overview of the Research on an Increasingly Widespread Pathogen - Greco, Davide; Aprile, Alessio; De Bellis, Luigi; Luvisi, Andrea (Frontiers in Plant Science, 2021)
Cultivated plants belonging to the genus Prunus are globally widespread and for some countries, are economically important crops; and they play a key role in the composition of a landscape. Xylella fastidiosa is a key threat to plant health, and several Prunus species are heavily stressed by this pathogen, such as almond, peach, and plum; many strain types of different subspecies can cause severe diseases. This review highlights different approaches to managing epidemic events related to X. fastidiosa in stone fruit plants. In fact, in most new European and Asian outbreaks, almond is the main and very common host and peach, plum, apricot, and cherry are widespread and profitable crops for the involved areas. Various diseases associated with stone fruit plants show different degrees of severity in relation to cultivar, although investigations are still limited. The development and selection of tolerant and resistant cultivars and the study of resistance mechanisms activated by the plant against X. fastidiosa infections seem to be the best way to find long-term solutions aimed at making affected areas recover. In addition, observations in orchards severely affected by the disease can be essential for collecting tolerant or resistant materials within the local germplasm. In areas where the bacterium is not yet present, a qualitative-quantitative study on entomofauna is also important for the timely identification of potential vectors and for developing effective control strategies.